Advertisement Remove all ads

Solve the Following Equation Using the Formula X^2 - 6x = 27 - Mathematics

Sum

Solve the following equation using the formula

`x^2 - 6x = 27`

Advertisement Remove all ads

Solution

`x^2 - 6x = 27`

`=> x^2 - 6x - 27 = 0`

Here a= 1, b= -6 and c = -27

Then `x = (-b +-  sqrt((-6)^2 - 4(1)(-27)))/(2(1))`

`= (6 -+ 12)/2 = (6 +12)/2 and (6 - 12)/2 = 9` and -3 

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 5 Quadratic Equations
Exercise 5 (D) | Q 1.01 | Page 64
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×